Neurobrucellosis mimicking demyelinizating disorders - Karaoglan, Ilkay; Akcali, Aylin; Ozkur, Ayhan; Namýduru, Mustafa (Annals of Saudi medicine, 2008)
On the physical exam, her temperature was 38°C, she was alert and cooperative, her left leg and arm muscle strength was 3/5, she had features of neck stiff--ness, and Kernig and Brudzinski signs. A lumbar puncture was performed; for the opening pressure was 280 mm Hg, 136 lymphocytes per mm 3 , 34 polymorphs per mm 3 , with 129 mg/dL protein, 33 mg/dL glucose (serum glucose was 95 mg/dL).